Levels of Reading Comprehension in Higher Education: Systematic Review and Meta-Analysis - de-la-Peña, Cristina; Luque-Rojas, María Jesús (Frontiers in Psychology, 2021)
Higher Education aims for university students to produce knowledge from the critical reflection of scientific texts. Therefore, it is necessary to develop a model of the situation of written information. The objective of this research was to determine through a systematic review and meta-analysis the proportion of university students who have an optimal performance at each level of reading comprehension. The systematic review of empirical studies is carried out from 2010 to March 2021 using the Web of Science, Scopus, Medline, PsycINFO databases. Two reviewers performed data extraction independently. A random-effects model of proportions was used for the meta-analysis and heterogeneity was assessed with I2. To analyze the influence of moderating variables, meta-regression was used and two ways were used to study publication bias. Seven articles were identified (n = 1044). The proportion of students at the literal level was 56% (95% CI: 39% - 72%, I2 = 96.3%), inferential level 33% (95% CI: 19% - 46%, I2 = 95.2%), critical level 22% (95% CI: 9% - 35%, I2 = 99.04%) and organizational level 22% (95% CI: 6% - 37%, I2 = 99.67%). Comparing reading comprehension levels, there is a significant higher proportion of university students who have an optimal level of literal compared to the rest of the reading comprehension levels. The results have to be interpreted with caution but are a guide for future research.